Mechanical, thermal, tribological, and flammability properties of polybutylene terephthalate composites: Comparing the effects of synthetic wollastonite nanofibers, natural wollastonite, and graphene oxide - Jia Xin Chan, Jia Xin Chan; Joon Fatt Wong, Joon Fatt Wong; Azman Hassan, Azman Hassan; Othman, Norhayani; Abd Razak, Jeefferie; Umar Nirmal, Umar Nirmal; Hashim, Shahrir; Yern Chee Ching, Yern Chee Ching; Yunos, Muhamad Zaini; Yahaya, Ridwan; T. M. Sampath U. Gunathilake, T. M. Sampath U. Gunathilake (Wiley, 2023)
Polybutylene terephthalate (PBT) composites were prepared with 1.0 phr synthetic wollastonite nanofibers (SWN), natural wollastonite (NW) and graphene oxide (GO) to study the effect of different fillers on mechanical, thermal, tribological, and flammability properties. The properties of PBT composites are related to the size, structure, and interfacial adhesion of the fillers in PBT matrix. PBT/SWN demonstrated the highest tensile strength and Young's modulus (6% and 9% increment), followed by PBT/NW (1.3% and 7% increment) and PBT/GO (2% decrement and 4% increment). PBT/SWN gave the highest degradation temperature (409C), followed by PBT/GO (404.7C). The maximum enhancement in wear resistance (73%) by PBT/SWN and anti-friction performance (26%) by PBT/GO evinced the excellent load-bearing ability of SWN and the great lubricating effect of GO. PBT/NW had the lowest peak heat release rate, smoke, and carbon dioxide production rate. This study shows that PBT composites have great potential in different automotive applications